2022
DOI: 10.1039/d2se00827k
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical water splitting with a triazine based covalent organic framework

Abstract: Photo electrochemical (PEC) water splitting under visible light irradiation is a very promising path for green and sustainable hydrogen production. PEC process has gained attracted enormous research interest due to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…The first-principles calculations showed that the effective electron–hole separation was achieved in TAPB-TTB COF due to strong donor–acceptor interaction compared to TTA-TTB COF. In line with this result, another report appeared in the literature, wherein two crystalline, 2D COFs were realized by Schiff base condensation of 1,3,5-tris­(4-formylbiphenyl)­benzene (TFBB) and 2,4,6-tris­(4-aminophenyl)-1,3,5-triazine (TAT) to yield TFBB–TAT, representing a D–A network . On the other hand, polycondensation of TFBB and 2,4,6-tris­(4-aminophenyl)­benzene (TAB) resulted in TFBB–TAB COF, representing a D-D type framework structure.…”
Section: Covalent Organic Framework-based Photochemical Electrochemic...mentioning
confidence: 60%
“…The first-principles calculations showed that the effective electron–hole separation was achieved in TAPB-TTB COF due to strong donor–acceptor interaction compared to TTA-TTB COF. In line with this result, another report appeared in the literature, wherein two crystalline, 2D COFs were realized by Schiff base condensation of 1,3,5-tris­(4-formylbiphenyl)­benzene (TFBB) and 2,4,6-tris­(4-aminophenyl)-1,3,5-triazine (TAT) to yield TFBB–TAT, representing a D–A network . On the other hand, polycondensation of TFBB and 2,4,6-tris­(4-aminophenyl)­benzene (TAB) resulted in TFBB–TAB COF, representing a D-D type framework structure.…”
Section: Covalent Organic Framework-based Photochemical Electrochemic...mentioning
confidence: 60%
“…16(a)). 115 Metal atom dispersed materials are considered as attractive electrocatalysts for water oxidation. COFs due to their porous structure are excellent platforms for embedding metal atoms.…”
Section: Environmental Applicationsmentioning
confidence: 99%
“…We further emphasize that many of these questions have applications that transcend the photoelectrochemistry of solar fuels and if resolved, have fundamental implications across a number of energy conversion and storage platforms. We focus here on PEC water splitting by soft photoelectrodes, but the questions raised are equally relevant to soft polymer PEC carbon dioxide reduction, which is a rapidly expanding field in its own right. While some issues highlighted here are also relevant to the emerging field of covalent organic frameworks (COFs) for PEC applications, we focus here on π-conjugated semiconducting polymers, and refer readers to related work focused on COFs. …”
Section: Scope Of This Perspectivementioning
confidence: 99%
“… 9 11 While some issues highlighted here are also relevant to the emerging field of covalent organic frameworks (COFs) for PEC applications, we focus here on π-conjugated semiconducting polymers, and refer readers to related work focused on COFs. 12 15 …”
Section: Scope Of This Perspectivementioning
confidence: 99%